Gene expression profiling of sex differences in HIF1-dependent adaptive cardiac responses to chronic hypoxia - Bohuslavová, Romana; Kolář, František; Kuthanová, Lada; Neckář, Jan; Tichopád, Aleš; Pavlinkova, Gabriela (Journal of applied physiology (Bethesda, Md., 2010)
Although physiological responses to chronic hypoxia, including pulmonary hypertension and right ventricular hypertrophy, have been well described, the molecular mechanisms involved in cardiopulmonary adaptations are still not fully understood. We hypothesize that adaptive responses to chronic hypoxia are the result of altered transcriptional regulations in the right and left ventricles. Here we report results from the gene expression profiling of adaptive responses in a chronically hypoxic heart. Of 11 analyzed candidate genes, the expression of seven and four genes, respectively, was significantly altered in the right ventricle of hypoxic male and female mice. In the transcriptional profile of the left ventricle, we identified a single expression change in hypoxic males (Vegfa gene). To directly test the role of HIF1, we analyzed the expression profile in Hif1a partially deficient mice exposed to moderate hypoxia. Our data showed that Hif1a partial deficiency significantly altered transcriptional profiles of analyzed genes in hypoxic hearts. The expression changes were only detected in two genes in the right ventricle of Hif1a(+/-) males and in one gene in the right ventricle of Hif1a(+/-) females. First, our results suggest that hypoxia mainly affects adaptive expression profiles in the right ventricle and that each ventricle can respond independently. Second, our findings indicate that HIF1a plays an important role in adaptive cardiopulmonary responses and the dysfunction of HIF1 pathways considerably affects transcriptional regulation in the heart. Third, our data reveal significant differences between males and females in cardiac adaptive responses to hypoxia and indicate the necessity of optimizing diagnostic and therapeutic procedures in clinical practice, with respect to sex.
Keywords: chronická nemoc; kardiomegalie; Adaptation, Physiological; Hypertension, Pulmonary; krevní tlak; sexuální faktory; Hypoxia; Vascular Endothelial Growth Factor A; Gene Expression Profiling; vaskulární endoteliální růstový faktor A; Mice, Knockout; Gene Expression Regulation; stanovení celkové genové exprese; Sex Factors; hypoxie; Blood Pressure; Female; srdeční komory; messenger RNA; RNA, Messenger; myši; Reverse Transcriptase Polymerase Chain Reaction; fyziologická adaptace; hematokrit; Mice; plicní hypertenze; Cardiomegaly; Chronic Disease; Disease Models, Animal; srdce - funkce komor; Ventricular Function; genetická transkripce; mužské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; zvířata; Mice, Inbred C57BL; Time Factors; ženské pohlaví; Hematocrit; Heart Ventricles; Animals; myši knockoutované; časové faktory; Male; tělesná hmotnost; modely nemocí na zvířatech; regulace genové exprese; Hypoxia-Inducible Factor 1, alpha Subunit; Transcription, Genetic; faktor 1 indukovatelný hypoxií - podjednotka alfa; myši inbrední C57BL; Body Weight